(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A person’s career choices and eventually, their entire life are influenced by their aspirations. It may be argued that having high expectations encourages people to put up significant effort to realize their objectives. Without taking into account the constraints or reality of the job market, occupational aspirations is a reflection of a person’s desire for their ideal employment. The degree of education, which gives the populace knowledge, authority, privilege, protection, and prestige, does, in fact, play a significant role in the advancement and development of tribal societies. Education is to have an impact and help bring about changes in the tribal community in the context of job aspirations. The main objective of the study was the compare of male and female undergraduate tribal students of University of Calcutta,Kolkata, West Bengal in relation to their occupational aspiration and the tools was used occupational aspiration scale developed by Prof. N.P. Chandel (2012). It revealed that there exists no significant difference in male and female undergraduate tribal students in relation to their occupational aspiration. In choosing their future careers, both undergraduate male and female tribal students share the similar ideals, aspirations, and desires.